Methods for assessing efficacy of cleaning and disinfection in livestock farms: a narrative review - Makovska, Iryna; Biebaut, Evelien; Dhaka, Pankaj; Korniienko, Leonid; Jerab, Julia Gabrielle; Courtens, Laura; Chantziaras, Ilias; Dewulf, Jeroen (Frontiers in Veterinary Science, 2025)
Cleaning and disinfection (C&D) procedures are essential components of farm biosecurity, aiming to reduce microbial load and eliminate the pathogenic microorganisms in livestock farms facilities. This review examines the various methods used to assess the effectiveness of both cleaning and disinfection, exploring their strengths, limitations, and optimal-use scenarios. For cleaning evaluation, common methods include basic visual inspections, ultraviolet (UV) fluorescence, adenosine triphosphate (ATP) bioluminescence, rapid protein tests (RPT), redox potential, and microbiological swabbing. However, visual inspections and UV fluorescence alone provide only qualitative insights. ATP offers quantitative data, though the accuracy can be influenced by the presence of detergents or disinfectants, requiring careful calibration. Additionally, ATP and RPT testing demands standardization to ensure consistent results. A new promising redox method is fast and more accurate, however still has limited field applicability. Microbiological methods, while highly accurate in detecting microbial contamination, are resource-intensive and therefore not in frequent use for routine evaluation of the cleaning procedures. For assessment of disinfection procedures microbiological tests such as colony-forming unit counts on agar plates, as well as the use of selective media for target microbes or hygiene indicator organisms are more appropriate than non-microbiological tests as they offer direct evidence of microbial elimination. However, these methods can be labor-intensive and time-consuming. Molecular methods can be powerful tools in detecting hard-to-culture organisms, however, are more expensive and require specialized equipment. Given these challenges, our study recommends a comprehensive C&D evaluation protocol, incorporating multiple methods tailored to the farm’s specific biosecurity needs and epidemiological context. This integrated approach improves the reliability and efficiency of C&D monitoring, ensuring robust hygiene management in farm settings.